2016
DOI: 10.18203/2320-1770.ijrcog20162123
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric hysterectomy: an emergency lifesaving procedure

Abstract: Background:Although rare in modern obstetrics, emergency peripartum hysterectomy (EPH) remains a life-saving procedure, in the event of uncontrollable postpartum hemorrhage. Observations regarding the causes and outcomes of EPH provide valuable insights relevant to the current management perspectives in obstetrics. This study is intended to assess the contemporary prevalence, indications, and outcomes of EPH, at a Tertiary care referral institute. Methods: A descriptive observational study was conducted as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
(32 reference statements)
1
8
1
Order By: Relevance
“…Total number of births in two years was 10,859. This is higher than other studies like Fatu F et al 0.8 per 1000, [2] 1.2 per 1000 by Shradha Shetty, [6] 0.83 per 1000 by Jaya Chawla [8] and 1 per 1000 by Meena N [9] . Our institute is tertiary care referral centre, with referrals from around the region.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Total number of births in two years was 10,859. This is higher than other studies like Fatu F et al 0.8 per 1000, [2] 1.2 per 1000 by Shradha Shetty, [6] 0.83 per 1000 by Jaya Chawla [8] and 1 per 1000 by Meena N [9] . Our institute is tertiary care referral centre, with referrals from around the region.…”
Section: Discussioncontrasting
confidence: 53%
“…The incidence of emergency obstetric hysterectomy is higher in the age group 25-35years [3-5, 7-13, 15, 16] and in grand multiparas. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . In our study too, incidence of emergency peripartum hysterectomies was found to be 50% in this age group and most were multiparas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These feelings are contrary to the ones of joy and gratitude which the women had hoped to experience following the birth of their children (10). In sub-Saharan Africa 1 in 200 women will loss their uterus through EPH due to severe PPH compared to the developed world of 1 in 1000 women (11)(12)(13). This is mainly due to lack of skilled attendance at birth, multiparity, prolonged and obstructed labour (14,15).…”
Section: Introductionmentioning
confidence: 99%